GP273 Corkambi: one year outcomes of orkambi on cystic fibrosis paediatric patients in cork university hospital. (June 2019) - O'Neill, Roisin; Chroinin, Muireann Ni; Mullane, David
Abstract : Introduction: Orkambi (Lumacaftor/Ivacaftor) was first introduced for use in the Cystic Fibrosis population in Ireland in 2017. It is only licensed for those patients who are homozygous for the F508del gene mutation.Orkambi was originally approved for children aged 12 years and older in 2017 and then this was extended for those aged 6–11 years old in 2018. Recently, the EMA(European Medicines Agency) has approved use for children 2–5 years. CUH(Cork University Hospital) looks after 98 paediatric patients with CF of whom 37 have been commenced on Orkambi since July 2017. Objectives: The primary objective was to assess the outcomes of Orkambi at 6 and 12 months on FEV1, BMI and BMI Centile and to compare the days on Intravenous antibiotics and weeks of oral antibiotics for pulmonary exacerbations in the year before and after commencing Orkambi. Results: Thirty seven patients were included in the study population with a split of 21 females and 16 males. The average profile of our patient cohort before commencing Orkambi was 11.0 years, BMI 16.8 kg/m2, BMI Centile 43.2 and Average FEV1 96.7%. To date, 11 patients have completed over a year of treatment and the remainder will have completed 12 months by June 2019. Six month followup has shown that 30/37(81%) of patients have had an increase in their BMI with an average BMI at 6 months of 17.5 and BMI difference of +0.7 kg/m2. BMI centile was increased in 24/37(65%) with centile difference of +5.7 to an average of 48.9. Lung function did not show any improvement from Pre-Orkambi values with average FEV1 of 95.9% at 6 months. This was also shown in followup of patients who completed 12 months of treatment with average FEV1 difference of -2%. For those who had completed 12 months on Orkambi, the no of weeks on oral antibiotics and IV antibiotics both showed a reduction in the year following commencement. There was a 26% decrease in oral antibiotics prescribed with average reduction of 1.5 weeks. Three patients had required IV antibiotics in the year prior. Two of these had no IVs over the following year and one patient with severe CF disease had a 55% reduction in days on IVs from 121 to 66 days. Conclusion: Orkambi has improved BMI/BMI centiles but has not shown any improvement in FEV1. Preliminary data has shown a reduction in pulmonary exacerbations although further analysis of the remaining patients will allow more accurate conclusions.